Coating of sulfur particles with manganese oxide nanowires as a cathode material in lithium-sulfur batteries - Lee, Jeongyeon; Hwang, Taejin; Lee, Yongho; Lee, Joong Kee; Choi, Wonchang (ELSEVIER SCIENCE BV, 2015)
alpha-MnO2 nanowires were synthesized by a hydrothermal method and then mixed with agglomerated sulfur powders. Homogeneous alpha-MnO2-coated sulfur particles were obtained by utilizing heat treatment intended to melt and recrystallize the sulfur. alpha-MnO2 nanowires lead to the suppression in re-agglomeration of sulfur powders during heat treatment and result in successful coating as well as decreased size in parent sulfur powders. The alpha-MnO2-coated sulfur particles were used as the cathode material for lithium-ion battery applications. Electrochemical evaluation such as the rate capability characteristics and impedance study indicates that the alpha-MnO2 coated sulfur cathode shows lower resistance and improved rate capability compared to a pristine sulfur cathode. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: LI-S BATTERIES; PERFORMANCE; COMPOSITE